Immigrants: your country needs them - Legrain, Philippe (London, 2006)
Immigration divides our globalising world like no other issue. We are swamped by bogus asylum-seekers and infiltrated by terrorists, our jobs stolen, our benefit system abused, our way of life destroyed - or so we are told. Philippe Legrain, author of the critically acclaimed OPEN WORLD, has written the first book that looks beyond the headlines. Why are ever-rising numbers of people from poor countries arriving in Europe, North America and Australasia? Can we keep them out? Should we even be trying? Combining compelling first-hand reporting from around the world, incisive socio-economic analysis and a broad understanding of what is at stake politically and culturally, IMMIGRANTS is a passionate, but lucid book. In our open world, more people will inevitably move across borders, Legrain says - and we should generally welcome them. They do the jobs we can't or won't do - and their diversity enriches us all. Left and right; free-marketeers and campaigners for global justice; enlightened patriots - all should rally behind the cause of freer migration, because They need Us and We need Them.
Keywords: Immigration